SnO2SnS2/graphene heterojunction composite promotes high-performance sodium ion storage - Yuanyuan Ma; Ke Ping; Peng Sun; Kaibin Lin; Junjie Guo; Lu Yue; Wenhui Zhang; Xiangwei Wu; Zhaoyin Wen (Journal of Materiomics)
The design of electrode material nanostructures including reducing material sizes and designing appropriate heterostructures, has great potential in improving charge storage dynamics and enhancing practical performance. In this study, we present the innovative synthesis of SnO2SnS2/graphene heterojunction composite materials via a controlled vulcanization reaction process. The unique structure endows the composite with high electronic conductivity, rapid ion diffusion rates, elevated electrochemical activity, excellent structural stability, and abundant reaction sites, making it a highly efficient anode material for sodium-ion batteries (SIBs). Half-cell tests demonstrate that the SnO2SnS2/r–G composite achieves a first Coulombic efficiency of 77.3% at a high current density of 5 A/g, showing remarkable cycling stability. Remarkably, the composite retains a reversible capacity of 330 mA⋅h/g after 1000 cycles, with a capacity retention rate of 77.5%. Moreover, we elucidate the specific sodium storage mechanisms of the heterojunction composite electrode via in-situ and ex-situ characterization methods. Furthermore, a full battery utilizing Na0.53MnO2 as the cathode and SnO2SnS2/r–G composite as the anode exhibits outstanding rate performance and long-term cycling stability. This method of heterostructure design and fabrication, coupled with the exceptional performance metrics, suggests that the SnO2SnS2/r–G heterostructure is a promising candidate for advanced anode materials in SIBs applications.